Orphans’ requirements in the social integration and employment - Lazarenko, V.; Lubyana, K. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The results of the research of the needs of orphan children in social integration as well as forms of work of social institutions assisting in complex life circumstances are presented in the article.